2021
DOI: 10.1111/acem.14221
|View full text |Cite
|
Sign up to set email alerts
|

Here to chair: Gender differences in the path to leadership

Abstract: Objective: Career paths leading to department chair positions are elusive. Women represent only 11% of academic emergency department (ED) chairs. It is unclear whether the pathway to chair is different for men and women; the characteristics, achievements, and qualifications among those who become ED chairs is unknown.Methods: This study is a cross-sectional analysis of curriculum vitae (CV) of current ED chairs in departments with Accreditation Council for Graduate Medical Education (ACGME)-accredited residenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…While women are underrepresented in executive leadership positions, education leadership roles did have a significantly greater representation of women compared to other leadership roles. This is similar to previous findings in the literature 21,22 . Future work should investigate education positions to learn if anything about these roles, systems, and/or processes can be used to increase the number of women in other leadership positions.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…While women are underrepresented in executive leadership positions, education leadership roles did have a significantly greater representation of women compared to other leadership roles. This is similar to previous findings in the literature 21,22 . Future work should investigate education positions to learn if anything about these roles, systems, and/or processes can be used to increase the number of women in other leadership positions.…”
Section: Discussionsupporting
confidence: 87%
“…This is similar to previous findings in the literature. 21,22 Future work should investigate education positions to learn if anything about these roles, systems, and/or processes can be used to increase the number of women in other leadership positions.…”
Section: Discussionmentioning
confidence: 99%
“…5 In EM, women faculty complete more subspecialty fellowship training and EM female chairs hold more advanced degrees, extramural funding, and national organization leadership positions than their male colleagues. 14 However, women in EM remain at disproportionately lower tiers of rank and pay for all ranks and quartiles of clinical load. 13,15 Despite these disparities, little is known about how women in EM become leaders or how their experiences differ from those of their male counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in other specialties have shown women, despite having higher qualifications and greater academic productivity than men, are underrepresented in leadership positions. This suggests that there may be differences in standards for promotion and appointment between men and women 12–14 . Underrepresentation of women in leadership positions despite their accomplishments has been observed across medicine and not limited to any one specialty 12,14 …”
Section: Accomplishmentsmentioning
confidence: 99%